Revisiting the Yorkshire Ripper Murders Histories of Gender, Violence and Victimhood - Wattis, Louise (Palgrave Studies in Victims and Victimology, 2018)
Between 1975 and 1980, Peter Sutcliffe, who became known as the Yorkshire Ripper, murdered 13 women in the North of England. The murders provoked widespread fear amongst women and impacted the public consciousness at both the local and national level. This book revisits the case, applying a feminist and cultural criminological lens to explore a range of criminological concerns relating to gender, violence and victimhood. Combining research findings from oral history interviews, analysis of popular criminological texts and academic commentary, this volume explores what the case can tell us about feminism, fear of crime, gender and serial murder and the representation of victims and sex workers. The volume contributes to a creative cultural criminology, highlighting how excavating recent criminal history and reading across texts presents new ways for understanding violence, gender and representation in the contemporary context. .